Epidemiologic characteristics of high-risk HPV and the correlation between multiple infections and cervical lesions - Qinli Luo; Xianghua Zeng; Hanyi Luo; Ling Pan; Ying Huang; Haiyan Zhang; Na Han (BMC Infectious Diseases, 2023)
Abstract Background The aim of this study was to determine the prevalence of high-risk human papillomavirus (HR-HPV) and the correlation between multiple infections and cervical lesions. Methods The current study involved population-based sample of 20,059 women who underwent cervical screening for 15 HR-HPV genotypes with ThinPrep cytologic test (TCT) results. The correlation between multiple HPV genotype infections and cervical lesions was also determined. The odds ratios (ORs) were calculated to assess co-infection patterns for each genotype with 15 other genotypes and the additive statistical interactions were evaluated. Results There was a bimodal pattern among multiple HPV infections, with a peak in the younger group and a second peak in the elderly group. Indeed, most multiple HPV genotypes exhibited a bimodal pattern. The most common HPV type in patients with high-grade squamous intraepithelial lesions (HSILs) was HPV-16, followed by HPV-52, HPV-58, and HPV-33. The most frequent HPV type in patients with cervical cancer was HPV-16, followed by HPV-58 and HPV-33. Women with multiple infections were at a increased risk of low-grade squamous intraepithelial lesions [LSIL] (OR = 2.01; 95% CI 1.38–2.93) and HSIL (OR 2.28; 95% CI 1.36–3.81) when compared to women with single infections. patients with cervical cancer had the higher percentage of multiple HPV infections. Based on the data herein, we suggest that HPV-33 and HPV-58 may also be high-risk HPV types worthy of increased surveillance and follow-up. Conclusion: Our findings suggested that the association between multiple HPV infections and HSIL and LSIL are stronger compared to single HPV infections. There may be some specific combinations that synergistically affected the risk of HSIL and LSIL.